Daya Predasi Myopopone castaneae (Hymenoptera :Formicidae) terhadap Larva Oryctes rhinoceros L. (Coleoptera : Scarabaidae) di Laboratorium The predation of Myopopone castaneae (Hymenoptera : Formicidae) to larvae of Oryctes rhinoceros L. (Coleoptera: Scar - Dhimas Junaedi; Darma Bakti; Fatimah Zahara (Universitas Sumatera Utara, 2015)
The objective of this research was to determine the effectiveness of Myopopone castaneaeto consumption larvae of Oryctes rhinoceros in the laboratory. This research was conducted fromDecember 2013 to February 2014 with altitude ± 25 above sea level in the Laboratory of Plant Pest,Faculty of Agriculture, University of Sumatra Utara. This research used randomizedcompletely design with 2 factors and 3 replications. The first factor was number of My. castaneae(0, 15, 20, and 25) and the second factor was larva’s instar (1, 2, and 3). The result showed that thehighest percentage of larva mortality was applicated by 25 of My. castaneae to larvae instar 1 ofO. rhinoceros (100%) in 3 days and the lowest was applicated by 15 of My. castaneae to larva’sinstar 3 of O. rhinoceros (20%). The highest consumption ability of My. castaneae is treatment usedlarva's instar 1 (applicated by 25, 20, and 15 of My. castaneae) that can consumpt 4-5 larva'sinstar 1 in five days, and the lowest is with using larva's instar 3 (applicated by 15, 20, and 25 ofMy. castaneae) that only can consumpt 1-2 larva's instar 3 of O. rhinoceros.Keywords: predation capacity, Myopopone castaneae, Oryctes rhinoceros L.